Microbial Recovery of Nickel and Cobalt from Pre-treated Chromite Overburdens of Sukinda Mines using Aspergillus niger - Panda and Lala Behari Sukla, Sunil Kumar Behera*, Prangya Parimita (Recent Research in Science and Technology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Aspergillus niger<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> <span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">exhibits good potential in generating a variety of metal chelating and solubilization organic acids during cellular metabolism. In this context, the minor constituent metals like nickel and cobalt embedded in chromite overburdens (COB) of Sukinda mines have been exploited through bio-hydrometallurgical route for recovery of these metal values. <span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">XRD and EPMA analysis of COB reveals that initially nickel was intertwined in the goethite lattice while after pre-treatment (600oC), due to phase conversion of goethite to hematite leads to exposure of nickel particles into the micro-pores and cracks developed in the matrix. Hence, becoming more susceptible to attack by the fungal bio acids and accelerates metal dissolution. At a pulp density of 2 % (w/v) of pre-treated COB maximum nickel and cobalt recovered were 33.2 % and 82.4 % respectively after 24 days in shake flasks bioleaching using A. niger.